2013
DOI: 10.1007/s11120-013-9855-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding chloroplast biogenesis using second-site suppressors of immutans and var2

Abstract: Chloroplast biogenesis is an essential light-dependent process involving the differentiation of photosynthetically competent chloroplasts from precursors that include undifferentiated proplastids in leaf meristems, as well as etioplasts in dark-grown seedlings. The mechanisms that govern these developmental processes are poorly understood, but entail the coordinated expression of nuclear and plastid genes. This coordination is achieved, in part, by signals generated in response to the metabolic and development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
73
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 145 publications
1
73
0
Order By: Relevance
“…The Isolation of Three New Virescent Mutants-We have carried out large scale ethyl methanesulfonate (EMS) and activation tagging mutagenesis looking for genetic suppressors of the Arabidopsis variegation mutant yellow variegated (var2) (44). During the screening process, we isolated a mutant that displayed both a leaf variegation phenotype typical of var2-5 and an additional virescent phenotype, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…The Isolation of Three New Virescent Mutants-We have carried out large scale ethyl methanesulfonate (EMS) and activation tagging mutagenesis looking for genetic suppressors of the Arabidopsis variegation mutant yellow variegated (var2) (44). During the screening process, we isolated a mutant that displayed both a leaf variegation phenotype typical of var2-5 and an additional virescent phenotype, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, FtsH2 has been observed to be attached to the thylakoid-associated polysomes, which are responsible for the translation of chloroplast-encoded membrane proteins like PsaA/B (Sirpiö et al, 2007). Furthermore, var2 suppressor screens have shown that the decreased translation rate caused by the secondary mutation in the var2 background leads to proper chloroplast development Putarjunan et al, 2013), which indicates that the functional role of FtsH2 is linked to the chloroplast translation machinery. Moreover, the chloroplast-encoded PSI assembly factor Ycf4 accumulated in high amounts in var1 and var2 plants (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although significant progress has been made toward our understanding of molecular mechanisms on chloroplast development, it still remains largely unclear how plastid and nuclear gene expressions are coordinately regulated. Leaf-variegated mutants, which display green sectors and nongreen sectors in the same leaf, are recognized as an ideal system for investigating the mechanisms of chloroplast formation (Liu et al, 2010c;Putarjunan et al, 2013). The prominent characteristic of variegation mutants is that the severity of leaf variegation depends on environmental and developmental cues.…”
mentioning
confidence: 99%
“…The prominent characteristic of variegation mutants is that the severity of leaf variegation depends on environmental and developmental cues. To date, a number of variegation mutants have been reported in Arabidopsis (Arabidopsis thaliana; for review, see Yu et al, 2007;Putarjunan et al, 2013). Among these mutants, variegated1 (var1), var2, and immutans (im) are well characterized.…”
mentioning
confidence: 99%